Envisioning The Well-Being of Indonesian General Insurance: Reflecting from The Retrenchment Strategy of Allianz Utama 2022 - Putra, Dony Sinanda (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
In the heat of commission war in Indonesian General Insurance industry at the end of 2021, PT Asuransi Allianz Utama Indonesia (the company) took a bold maneuver to stop competing in the high-acquisition-cost market. The company did not stop operating, but consciously executing a significant downsize in targeting due to the exit from the unhealthy market in the motor and property line in Brokers and agency distribution channel. This brave retrenchment strategy resulted in a successful company turnaround in 2022. This study aims to evaluate the effectiveness of this maneuver as a best practice sharing in the industry that is very much needed. The novelty of this study is the first in Indonesian General Insurance retrenchment case. This study became urgent due to the company having made a successful turnaround and needing to decide on the strategy going forward. The method used is primary data interview and secondary data document review to create SWOT matrix analysis for strategy formulation. This study concludes that the retrenchment was a must do maneuver and very much aligned with the condition and strategy fit in the company. Aside from contributing to the company, this study could also contribute to regulator and players in the industry, as a real case example about walking away from saturated market and grabbing untapped opportunities by capitalizing one’s unique strength. It is a recommended strategy for the market players in Indonesian general insurance industry. Also, as the first study in Indonesian general insurance strategy, the implication of this study can become a trigger to a lot of strategic research in the vast Indonesian general insurance field.